Recursos directamente recaudados y su incidencia en la ejecución presupuestal de la Municipalidad Provincial de Maynas, periodo 2018 – 2022 - Ushiñahua Ihuaraqui, Cesar Augusto (2023)
The research work called "Directly Collected Resources and their incidence in the budgetary execution of the MPM, period 2018 - 2022", has the purpose of analyzing the origin of the collection of income and expenses of the financing source resources directly collected and its influence, which can be seen in budget execution, to then propose policies and guidelines that contribute to better collection of directly collected resources. The methodology used is a quantitative approach of a descriptive explanatory type. The technique of data collection and information gathering will be implemented through the MEF transfer portal, as well as a review of specialized bibliography, newspapers and magazines. The research work was developed obtaining information from the official portal of the Ministry of Economy and Finance where you can have updated and verified data on the Provincial Municipality of Maynas, where statistical programs were applied for data processing and thus be able to obtain the results of research and therefore its analysis. In accordance with the analysis methodology, it was concluded that, thanks to the collection of Resources Directly Collected by the Provincial Municipality of Maynas, it was possible to fulfill the goals and objectives programmed in the (POI) Institutional Operational Plan.